Direction: Study the following questions carefully and choose the right answer.
1
When 2x +  2  = 3, then value of x3 +  1  + 2 is
x x3
» Explain it
B
Given,

2x +  2  = 3
x

or   ( x +  1 )  =  3
x 2

Cubing both sides, we get

x3 +  1  + 3 ( x +  1 )  =  27
x3 x 8

or, x3 +  1  + 3×  3  =  27
x3 2 8

or, x3 +  1  =  27  –  9  =  –  9
x3 8 2 8

or, x3 + 1  + 2 = 2 –  9  ⇒  7
x3 8 8

Hence, option B is correct.

2
If x = 332, y = 333, z = 335 then the value of x3 + y3 + z3 – 3xyz = ?
» Explain it
C
∵    (x3 + y3 + z3 – 3xyz) = (x + y + z) (x2 + y2 + z2 – xy – yz – zx)

=   (x + y + z)× 1  [(x – y)2 + (y – z)2 + (z – x)2]
2

On putting the values, we get

=  1000 ×  1  [(332 – 333)2 + (333 – 335)2 + (335 – 332)2
2
 
=  1000 ×  1  [1 + 4 + 9]
2

=  7000

Hence, option C is correct.

3
If x +  1  = 5, then  2x  is equal to
x 3x2 – 5x + 3
» Explain it
B
x +  1  = 5
x

⇒   x2 – 5x + 1 = 0

Equation multiplied by 3, then 

⇒   3x2 – 15x + 3 = 0       ⇒   3x2 + 3 = 15x   

∴      2x  =  2x
3x2 – 5x + 3 15x – 5x

=   2x  =  1
10x 5

Hence, option B is correct.

4
If ab + bc + ca = 0, then the value of

 
1
a2 – bc
 + 
1
b2 – ac
 + 
1
c2 – ab
 is
» Explain it
C
ab + bc + ca = 0

⇒ ab + ca = –bc

∴     a2 – bc = a2 + ab + ca = a(a + b + c)

Similarly,

b2 – ac = b(a + b + c)

c2 – ac = c(a + b + c)

∴   
1
a2 – bc
 + 
1
b2 – ac
 + 
1
c2 – ab

=    1  +  1  +  1
a(a + b + c) b(a + b + c) c(a + b + c)

=    bc + ac + ab  = 0
abc(a + b + c)

Hence, option C is correct.

5
If x = 2 then the value of x3 + 27x2 + 243x + 631 is:
» Explain it
C
Given equation,

f(x) = x3 + 27x2 + 243x + 631

⇒  x(x2 + 27x+ 243) + 631

Now, put the value of x = 2

⇒  2(22 + 27 × 2 + 243) + 631

⇒  2 (4 + 54 + 243) + 631

⇒  2(301) + 631 = 602 + 631 = 1233.